Preparation method and application of Ni3S2-Ni (OH) 2 heterostructure nanosheet catalyst
By hydrothermal growth of Ni(OH)2 on a foamed nickel substrate and introducing sodium sulfide, Ni3S2-Ni(OH)2 heterostructured nanosheet catalyst was formed, and the problem of high surface reconstruction energy barrier of the nickel-based catalyst was solved, and a high activity and stability of ammonia decomposition catalytic effect was achieved.
Patent Information
- Application Number
- CN202510072890.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The energy barrier of existing nickel-based catalysts to form active substances in surface reconstruction during ammonia oxidation reactions limits the improvement of catalytic activity.
Ni(OH)2 was grown in situ on the foamed nickel substrate by hydrothermal method, and sodium sulfide was introduced through anion exchange reaction to form a Ni3S2-Ni(OH)2 heterostructure nanosheet catalyst.
The energy barrier for the catalyst surface reconstruction is reduced, the catalytic activity and stability are improved, and the excellent ammonia decomposition efficiency is achieved under alkaline conditions.
Smart Images

Figure CN119746889A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of heterogeneous structure material synthesis and electrocatalysis technology, and specifically to a simple strategy based on a hydrothermal method to prepare Ni 3 S 2 -Ni(OH) 2 Heterostructured nanosheet catalysts and their applications as electrodes in electrocatalytic ammonia decomposition. Background Art
[0002] As the requirements for low-carbon emission reduction continue to increase, hydrogen as a zero-carbon energy carrier has received more and more attention. However, the high storage cost and low safety factor of hydrogen are issues that cannot be ignored in its application. Among the many hydrogenated substances that can store or even replace hydrogen energy, ammonia has attracted widespread attention due to its high hydrogen storage capacity, low liquefaction storage energy consumption, and low theoretical electrolysis voltage. Under alkaline conditions, using the electrocatalytic ammonia oxidation reaction as the anode of the electrolyzer is currently a scientific and efficient hydrogen conversion method. Traditional precious metal materials (such as platinum and ruthenium) have been widely studied as efficient catalysts for ammonia electrooxidation, but their high cost and easy to be N ads The passivation problem hinders its large-scale application. Therefore, it is urgent to develop non-precious metal catalysts with high activity and stability.
[0003] Nickel-based materials are potential substitutes for precious metal catalysts due to their simple preparation, environmental protection, low cost, abundant reserves, and excellent performance. Among them, nickel layered hydroxides have ultra-thin layered structures, adjustable host layers / interlayers, and are not easily oxidized by N under alkaline conditions. ads The ability of Ni(OH) to poison has been widely studied. 2 NiOOH reconstructed after voltage application is the real catalytically active substance, but the high energy barrier for surface reconstruction hinders further improvement of catalytic activity. Therefore, it is very necessary to rationally prepare ammonia decomposition catalysts that reconstruct rapidly and have high activity and stability. Summary of the invention
[0004] The object of the present invention is to provide a Ni 3 S 2 -Ni(OH) 2 A heterogeneous structure nanosheet catalyst and its preparation method and application, thereby solving the problem that the energy barrier of the nickel-based catalyst in the existing ammonia oxidation reaction that the surface is reconstructed to form active substances limits the catalytic activity.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a Ni for ammonia oxidation reaction 3 S 2 -Ni(OH)2 The preparation method of heterostructured nanosheets is to first grow Ni(OH) in situ on a nickel foam substrate by a hydrothermal method. 2 Then, through anion exchange reaction, the active sulfur anions released by sodium sulfide partially replace the hydroxide anions in the nickel hydroxide nanosheet array, thereby forming Ni 3 S 2 -Ni(OH) 2 Heterogeneous structure material, comprising the following steps:
[0007] Step 1: Pretreatment of nickel foam
[0008] The nickel foam was sequentially washed with 3mmol / L hydrochloric acid, anhydrous ethanol, and ultrapure water for 30 minutes and then dried in a vacuum oven to serve as a conductive substrate.
[0009] Step 2: Preparation of reaction solution A
[0010] Take appropriate amounts of anhydrous nickel chloride, ammonium fluoride and urea and dissolve them in ultrapure water. After magnetic stirring for 30 minutes, a uniform reaction solution A is obtained.
[0011] Step 3: Ni(OH) 2 Preparation of nanosheets
[0012] The cleaned nickel foam is immersed in solution A and transferred to a hydrothermal reactor for the first hydrothermal reaction. After the reactor is cooled down, the material is taken out, rinsed with ethanol and ultrapure water for multiple times to remove unreacted residues, and placed in a vacuum oven for drying;
[0013] Step 4: Preparation of reaction solution B
[0014] Dissolve an appropriate amount of sodium sulfide nonahydrate in ultrapure water and stir magnetically for 10 minutes to obtain a uniform reaction solution B;
[0015] Step 5: Ni 3 S 2 -Ni(OH) 2 Preparation of heterostructured nanosheets
[0016] The loaded Ni(OH) prepared in step 3 2 The nickel foam was immersed in the reaction solution B and transferred to the hydrothermal reactor for the second step of hydrothermal reaction. After the reactor cooled down, the material was taken out, rinsed with ethanol and ultrapure water several times to remove the unreacted residues, and placed in a vacuum oven for drying to obtain the final Ni loaded on the surface of the nickel foam. 3 S 2 -Ni(OH) 2 Heterostructured nanosheets.
[0017] Preferably, the amounts of anhydrous nickel chloride, ammonium fluoride and urea added to the reaction solution A are 2 mmol, 6 mmol and 12 mmol respectively, and the amount of ultrapure water is 30 mL.
[0018] Preferably, the amount of sodium sulfide nonahydrate added to the reaction solution B is 0.9 mmol, and the amount of ultrapure water is 30 mL.
[0019] Preferably, the conditions for the first hydrothermal reaction are 120° C. and 6 hours.
[0020] Preferably, the conditions of the second step hydrothermal reaction are 160° C. and 8 hours.
[0021] Preferably, the heterostructure is in the shape of a lamellar structure grown vertically on the surface of the nickel foam.
[0022] A Ni prepared by the present invention 3 S 2 -Ni(OH) 2 Application of heterostructured nanosheet catalysts in ammonia electrooxidation.
[0023] The Ni 3 S 2 -Ni(OH) 2 When heterogeneous electrocatalysts are used for ammonia oxidation reaction, Ni 3 S 2 -Ni(OH) 2 The heterogeneous structure nanosheet catalyst was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, and the carbon rod was used as the counter electrode. The catalyst can achieve a voltage of 1.7 V and a charge of 207 mA cm-2 in the ammonia oxidation reaction under alkaline conditions. -2 The current density is high and it shows good stability.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] The present invention provides a Ni 3 S 2 -Ni(OH) 2 The synthesis method of heterogeneous structured nanosheets uses nickel foam with a three-dimensional porous structure as a conductive substrate to in situ grow uniform Ni 3 S 2 -Ni(OH) 2 Heterostructured nanosheets have simple synthesis steps, high preparation efficiency and are environmentally friendly.
[0026] The present invention provides a Ni 3 S 2 -Ni(OH) 2The application of heterogeneous structure catalysts in ammonia electrooxidation reaction effectively ensures the rapid diffusion of ions due to the hierarchical porous structure of nickel foam; the ultra-thin nanosheet structure provides a larger electrochemical active area, exposing more active sites, and has excellent catalytic activity in alkaline solutions containing ammonia, effectively improving the efficiency of ammonia decomposition.
[0027] The Ni provided by the present invention 3 S 2 -Ni(OH) 2 During the electrocatalytic process, the heterogeneous structure formed by sulfur doping adjusts the electronic structure of the catalyst, reduces the energy barrier of surface reconstruction, and enables the catalyst to be quickly reconstructed into the active substance Ni for the ammonia electrooxidation reaction. 3 S 2 -NiOOH provides a new idea for solving the problem of high reconstruction energy barrier of nickel-based catalysts.
[0028] The Ni provided by the present invention 3 S 2 -Ni(OH) 2 Heterostructured catalysts have strong stability and their performance shows almost no attenuation after long-term catalytic ammonia electrooxidation reaction. They also have excellent catalytic activity, which is of great significance for the further development and assembly of efficient and stable electrocatalytic ammonia decomposition systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 SEM image of heterostructured nanosheets.
[0030] Figure 2 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 High-resolution TEM image of heterostructured nanosheets.
[0031] Figure 3 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 XRD patterns of heterostructured nanosheets.
[0032] Figure 4 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 The heterogeneous nanosheet catalysts were exposed to 1.0 M KOH and 1.0 M KOH + 0.5 M NH 3 Comparison of CV scans in electrolyte.
[0033] Figure 5 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 Heterostructured catalyst in 1.0M KOH+0.5M NH 3 Stability test graph in electrolyte and LSV scan comparison graph before and after stability test.
[0034] Figure 6 Ni prepared in the present invention 3 S 2 -Ni(OH) 2 Heterogeneous structure catalyst and comparative example 1 (Ni(OH) 2 -NF) and Comparative Example 2 (Ni 3 S 2 -NF) in 1.0 M KOH + 0.5 M NH 3 Comparison of LSV scans in electrolyte. DETAILED DESCRIPTION
[0035] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0036] Example 1
[0037] Ni 3 S 2 -Ni(OH) 2 Heterostructured nanosheets are synthesized in the following steps:
[0038] Step 1: Pretreatment of nickel foam
[0039] Cut the nickel foam into 3*4cm 2 size, and ultrasonically washed with 3mmol / L hydrochloric acid, anhydrous ethanol, and ultrapure water for 30 minutes in sequence, and dried in a vacuum oven at 60°C to serve as a conductive substrate;
[0040] Step 2: Preparation of reaction solution A
[0041] Accurately weigh 2 mmol of anhydrous nickel chloride, 6 mmol of ammonium fluoride and 12 mmol of urea and dissolve them in 30 mL of ultrapure water. After magnetic stirring for 30 minutes, a uniform reaction solution A is obtained.
[0042] Step 3: Ni(OH) 2 Preparation of nanosheets
[0043] The cleaned nickel foam was immersed in solution A and transferred to a hydrothermal reactor, heated to 120°C and maintained for 6 hours. After the reactor cooled down, the material was taken out, rinsed with ethanol and ultrapure water several times to remove unreacted residues, and dried in a vacuum oven at 60°C.
[0044] Step 4: Preparation of reaction solution B
[0045] Accurately weigh 0.9 mmol of sodium sulfide nonahydrate and dissolve it in 30 mL of ultrapure water. After magnetic stirring for 10 minutes, a uniform reaction solution B is obtained.
[0046] Step 5: Ni 3 S 2 -Ni(OH) 2 Preparation of heterostructured nanosheets
[0047] The loaded Ni(OH) prepared in step 3 2 The nickel foam nanosheets were immersed in the reaction solution B and transferred to the hydrothermal reactor, heated to 160 °C and maintained for 8 hours. After the reactor cooled down, the material was taken out, rinsed with ethanol and ultrapure water several times to remove the unreacted residues, and dried in a vacuum oven at 60 °C to obtain the final Ni 3 S 2 -Ni(OH) 2 Heterostructured nanosheet materials.
[0048] The Ni prepared in this example 3 S 2 -Ni(OH) 2 The microstructure and XRD spectra of heterostructured nanosheets are shown in Figure 2. Figure 1 , 2 , as shown in Figure 3.
[0049] Example 2
[0050] Ammonia electrooxidation reaction performance test. The test steps are as follows:
[0051] Cut the nickel foam loaded with catalyst into 1*2cm 2 The size was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, the carbon rod was used as the counter electrode, and 1.0 M KOH and 1.0 M KOH + 0.5 M NH 3 The solution was used as the electrolyte to construct a three-electrode system electrolytic cell for ammonia electrooxidation reaction testing.
[0052] Apply voltage to the working electrode (1.0-1.7V vs. RHE), Ni 3 S 2 -Ni(OH) 2 The heterostructured nanosheets exhibited a high current density in the ammonia electrooxidation reaction. Figure 4 For you 3 S 2 -Ni(OH) 2 The heterogeneous catalysts were heated in 1.0 M KOH and 1.0 M KOH + 0.5 M NH 3 Comparison of CV scans in electrolyte.
[0053] Apply 10 mA cm to the working electrode. -2 The constant current of Ni 3 S 2 -Ni(OH) 2 The heterostructured nanosheets can operate stably for 24 hours in the ammonia electrooxidation reaction, and the current density after the stability test does not decrease significantly compared to before the test, showing good stability. Figure 5 For you 3 S 2 -Ni(OH) 2 Heterostructured catalyst in 1.0M KOH+0.5M NH 3 Stability test graph in electrolyte and LSV scan comparison graph before and after stability test.
[0054] Comparative Example 1
[0055] In situ growth of Ni(OH) on nickel foam 2 The preparation method of the nanosheets is as follows:
[0056] Accurately weigh 2 mmol of anhydrous nickel chloride, 6 mmol of ammonium fluoride and 12 mmol of urea and dissolve them in 30 mL of ultrapure water. After magnetic stirring for 30 minutes, a uniform reaction solution A is obtained.
[0057] The cleaned nickel foam was immersed in solution A and transferred to a hydrothermal reactor, heated to 120°C and maintained for 6 hours. After the reactor cooled down, the material was taken out, rinsed with ethanol and ultrapure water several times to remove unreacted residues, and placed in a vacuum oven at 60°C for drying.
[0058] Comparative Example 2
[0059] In situ growth of Ni on nickel foam 3 S 2 The preparation method of the nanosheets is as follows:
[0060] Accurately weigh 0.9 mmol of sodium sulfide nonahydrate and dissolve it in 30 mL of ultrapure water. After magnetic stirring for 10 minutes, a uniform reaction solution B is obtained.
[0061] The cleaned nickel foam was immersed in solution B and transferred to a hydrothermal reactor, heated to 160°C and maintained for 8 hours. After the reactor cooled down, the material was taken out, rinsed with ethanol and ultrapure water several times to remove unreacted residues, and placed in a vacuum oven at 60°C for drying.
[0062] See also Figure 6 , which shows that Ni 3 S 2 -Ni(OH) 2 Electrocatalytic performance of heterostructured nanosheets and comparative samples for ammonia oxidation in alkaline medium containing ammonia. LSV polarization curves show that Ni 3 S 2 -Ni(OH) 2 The current density of the heterostructured nanosheets at 1.7 V is much higher than that of Ni(OH) 2 / NF and Ni 3 S 2 / NF, indicating Ni 3 S 2 and Ni(OH) 2 The interfacial synergy between the catalysts not only provides more active sites but also promotes the rapid surface reconstruction of the catalyst, resulting in good electrocatalytic ammonia oxidation performance.
[0063] In summary, the embodiments of the present invention provide Ni 3 S 2 -Ni(OH) 2 The advantages of heterogeneous structure nanosheet catalyst and its preparation method and application are: the synthesis steps are simple and efficient; the prepared catalyst effectively ensures the rapid diffusion of ions due to the graded porous structure of nickel foam; the ultra-thin nanosheet structure provides a larger electrochemical active area and exposes more active sites; the heterogeneous structure formed by sulfur doping adjusts the electronic structure of the catalyst, reduces the energy barrier of surface reconstruction, and significantly improves the catalytic activity of the material; the performance is almost unchanged under long-term catalytic ammonia decomposition reaction operation, and has high stability. It can be used as a catalytic electrode in electrochemical ammonia oxidation reaction, effectively improving the efficiency of ammonia decomposition, and has broad application prospects.
[0064] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing Ni3S2-Ni(OH)2 heterostructure nanosheets, firstly in situ growing Ni(OH)2 on a nickel foam substrate by a hydrothermal method, and then by anion exchange reaction, allowing the active sulfur anions released by sodium sulfide to partially replace the hydroxide anions in the nickel hydroxide nanosheet array, thereby forming a Ni3S2-Ni(OH)2 heterostructure material, comprising the following steps: Step 1: Pretreatment of nickel foam The nickel foam was sequentially washed with 3mmol / L hydrochloric acid, anhydrous ethanol, and ultrapure water for 30 minutes and then dried in a vacuum oven to serve as a conductive substrate. Step 2: Preparation of reaction solution A Take appropriate amounts of anhydrous nickel chloride, ammonium fluoride and urea and dissolve them in ultrapure water. After magnetic stirring for 30 minutes, a uniform reaction solution A is obtained. Step 3: Preparation of Ni(OH)2 nanosheets The cleaned nickel foam is immersed in solution A and transferred to a hydrothermal reactor for the first hydrothermal reaction. After the reactor is cooled down, the material is taken out, rinsed with ethanol and ultrapure water for multiple times to remove unreacted residues, and placed in a vacuum oven for drying; Step 4: Preparation of reaction solution B Dissolve an appropriate amount of sodium sulfide nonahydrate in ultrapure water and stir magnetically for 10 minutes to obtain a uniform reaction solution B; Step 5: Preparation of Ni3S2-Ni(OH)2 heterostructure nanosheets The Ni(OH)2 loaded nickel foam prepared in step 3 is immersed in reaction solution B and transferred to a hydrothermal reactor for the second hydrothermal reaction. After the reactor is cooled down, the material is taken out, rinsed with ethanol and ultrapure water several times to remove unreacted residues, and placed in a vacuum oven for drying to obtain the final Ni3S2-Ni(OH)2 heterostructure nanosheets loaded on the surface of the nickel foam.
2. The method for preparing the Ni3S2-Ni(OH)2 heterostructure nanosheet according to claim 1, characterized in that: The amounts of anhydrous nickel chloride, ammonium fluoride and urea added to the reaction solution A were 2 mmol, 6 mmol and 12 mmol, respectively, and the amount of ultrapure water was 30 mL.
3. The method for preparing the Ni3S2-Ni(OH)2 heterostructure nanosheet according to claim 1, characterized in that: The amount of sodium sulfide nonahydrate added to the reaction solution B was 0.9 mmol, and the amount of ultrapure water was 30 mL.
4. The method for preparing the Ni3S2-Ni(OH)2 heterostructure nanosheet according to claim 1, characterized in that: The conditions for the first hydrothermal reaction were 120°C for 6 hours.
5. The method for preparing the Ni3S2-Ni(OH)2 heterostructure nanosheet according to claim 1, characterized in that: The conditions of the second step hydrothermal reaction were 160°C for 8 hours.
6. The method for preparing the Ni3S2-Ni(OH)2 heterostructure nanosheet according to claim 1, characterized in that: The heterogeneous structure is in the shape of a lamellar structure vertically grown on the surface of the nickel foam.
7. Use of the Ni3S2-Ni(OH)2 heterostructure nanosheet catalyst according to any one of claims 1 to 6 in ammonia electrooxidation reaction.
8. The use according to claim 7, characterized in that: When the Ni3S2-Ni(OH)2 heterostructure electrocatalyst is used for ammonia oxidation reaction, under alkaline conditions containing ammonia, the Ni3S2-Ni(OH)2 heterostructure nanosheet catalyst is used as a working electrode, the Hg / HgO electrode is used as a reference electrode, and the carbon rod is used as a counter electrode.
Citation Information
Patent Citations
Preparation method and application of nickel hydroxide supported palladium monatomic catalyst
CN115555031A
Iron and molybdenum co-modified nickel sulfide nanosheet array as well as preparation method and application thereof
CN116590739A
Preparation method of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst and application of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst in hydrogen production
CN118480812A
Cited By
Supported sulfur-doped nickel-based hydroxide nano array as well as preparation method and application thereof
CN122057535A